Model predictive control of a bidirectional AC-DC converter for V2G and G2V applications in electric vehicle battery charger - Parvez M.; Mekhilef S.; Tan N.M.L.; Akagi H. (Institute of Electrical and Electronics Engineers Inc., 2023)
This paper presents a model predictive control algorithm of three-phase bidirectional AC-DC converter that can be used for V2G and G2V applications. This algorithm utilizes the discrete behaviour of the converter to determine appropriate switching states that minimize the cost function. The proposed predictive control scheme allows bidirectional power transfer with instantaneous mode changing capability and fast dynamic response. This paper also presents the results simulated with MATLAB/Simulink and further validated with a 1.5 kW experimental set-up to confirm the feasibility of the proposed control scheme. Both the simulation and experimental results prove that the converter is operated with sinusoidal grid current, acceptable THD, unity power factor and contain very low voltage ripples in the DC side. © 2014 IEEE.